The role of albumin and the extracellular matrix on the pathophysiology of oedema formation in severe malnutrition - Gonzales, GB; Njunge, JM; Gichuki, BM; Wen, B; Ngari, M; Potani, I; Thitiri, J; Laukens, D; Voskuijl, W; Bandsma, R; Vanmassenhove, J; Berkley, JA (Elsevier, 2022)
Background While fluid flows in a steady state from plasma, through interstitium, and into the lymph compartment, altered fluid distribution and oedema can result from abnormal Starling's forces, increased endothelial permeability or impaired lymphatic drainage. The mechanism of oedema formation, especially the primary role of hypoalbuminaemia, remains controversial. Here, we explored the roles of albumin and albumin-independent mechanisms in oedema formation among children with severe malnutrition (SM).